Penerapan Model Pembelajaran Berbasis Kasus pada Mata Kuliah Mekanika untuk mendukung Pembelajaran Jarak Jauh - Restianingsih, Tika; Nurhidayah, Nurhidayah; Handayani, Linda (COMPTON: Jurnal Ilmiah Pendidikan Fisika, 2022)
A case-based learning method has been implemented in the mechanics course. Learning activity is carried out online through the Universitas Jambi e-learning website and Zoom Meeting platform. This method produces learning instruments, namely learning outcomes for graduates of mechanics courses, syllabus and lecture contracts, Semester Lesson Plans, Student Project Task Plans, and Learning Outcomes Assessment Sheets for case-based learning models reviewed. This research was accomplished through the observation and evaluation stages. The observations are carried out by observing the class activities, starting with the stages of finding cases, solving cases, presenting the solved cases in front of the class, and discussing. The results of the student satisfication questionnaire about the learning method used indicate the evaluation stage. The questionnaire results showed that more than 80% of students were satisfied and interested in the case-based learning method.